Evolution of Microstructure and Wear Resistance of Carburized Low Carbon Steel - Wongtimnoi, Komkrisd; Chowwanonthapunya, Thee (International Journal of Integrated Engineering, 2022)
The main aims of this present work were to investigate the microstructure and wear resistance of AISI 1020 during the pack carburization. The samples were prepared in a rectangular shape with a dimension of 5 mm X 25 mm X 2 mm for microstructure and hardness studies. Another set of samples with a dimension of 4.0 cm x 2.5 cm x 0.5 cm was prepared for the wear resistance performance. Both sets of samples were packed in the steel container which was tightly sealed. The carburizing atmosphere in the container was prepared by using mixtures of powdered charcoal and tamarind catalysts. The carburizing temperature of 950 Â°C with a fixed carburizing time of 2 hours was controlled for the pack carburizing treatment. The results exhibited that in the fresh condition, AISI 1020 mostly contained ferrite. Nevertheless, after carburization, quenching, and tempering process were carried out, the microstructures of the samples were changed from ferrite to pearlite and then martensite. An increase in the carbon content after carburization plays a major role in the evolution of the high hardness layers which subsequently enhanced the hardness and the wear resistance performance of AISI1020 after quenching and tempering.